Mechanism of the Application of Strategic Planning and Impact on the Development of the Economic Plan 2030 in the Kingdom of Bahrain - qalbein, Ahmed Mohammed Abu (International Journal of Psychosocial Rehabilitation, 2020)
Application of strategic planning plays an important role on the development of economic plan of any country. However, rapid economic and industrial changes as well as population growth in Bahrain are integral part of strategic planning. This research aimed to explore the impact of strategic planning on the development of the economic plan 2030 in the Kingdom of Bahrain. Additionally, not enough research has been conducted to ascertain the impacts of strategic planning on the development of economic plan in Bahrain. To do so, a structured survey was conducted for receiving observations of 384 government officials in Bahrain and to analyse the effect. The data is analysed and hypothesis is tested by using IBM-SPSS-AMOS package 25.0. The study found that the direct effects of strategic planning on the development of economic plan in Bahrain are positive and significant. The originality of the manuscript goes back to studying the concept in the Arab world. On the basis of the result, this research endorsed that, the development in Bahrain is heavily in line with consistent growth of industrialization and it was proposed to apply to the actors involved who work for Bahrain’s Government Work the strategic planning and project management framework and to improve the know-how of government ministries and organisations with a view to executing the overall KBM processes.